Contributions of Professor M. Kabir Hassan to the Islamic finance literature : a bibliometric study - Mukit, Mohammad Mushfiqul Haque; Muneeza, Aishath; Paltrinieri, Andrea (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study presents Professor M. Kabir Hassan’s productivity, citations, collaborations with fellow researchers, publications, and content analysis with future research direction in conjunction with his 30th academic anniversary which is marked in 2021. The bibliometric and thematic analysis of the scientific legacy of Professor M. Kabir Hassan was conducted based on his publications from 1991 to 2021. During his long career, he has published 346 journal articles with 23,059 citations and collaborated with 292 authors globally. The findings of conceptual and empirical research papers published by Professor M. Kabir Hassan are crucial for the theoretical developments of Islamic finance, as well as its practical developments as a distinctive discipline. We have derived several research areas for future research based on the research works published by Professor M. Kabir Hassan, as follows: i) the issue of Islamic common market that needs to be examined further in the light of new data and changing global perspectives; ii) a study on the issues faced by Islamic banks in adopting Basel III and capital adequacy framework for Islamic banks; iii) new models for takaful need to be explored; iv) the cost of faith-based investing needs to be studied in the recent times, especially to understand the impact of the pandemic on it; v) a study to understand the perception of the government of Bangladesh, and international and multilateral organisations on the role of zakat to alleviate poverty; vi) the level of technology adoption by Islamic banks can be studied; and vii) the successful implementation of equity-based Islamic finance contracts could be empirically studied.. It is anticipated that this research will motivate young and emerging scholars, as well as existing scholars, to excel in their arenas by producing quality research and publications in a consistent manner.